The Intergration of Regional Defense and Development Based on Information Technology - Poespitohadi, Wibisono; Zauhar, Soesilo; Haryono, Bambang Santoso; Amin, Fadillah; Fanani, Zaenal; Hermawan, Romy (International Journal of Psychosocial Rehabilitation, 2020)
This study was designed to obtain an understanding of Defense forces Integrating Spatial Plans with Bandung City Spatial Plans to Resilience Areas. The aim of the study were; First, it was to assess the implementation of integration of Spatial Planning Forces with Bandung City Spatial Planning. Second, it was to assess the obstacles faced in integration of Defense Forces Spatial Planning with Bandung Regional Spatial Planning. Last, it was to assess efforts for Defense Planning Planning integration Spatial planning with City Spatial area so that Resilience in Bandung City. The research method employer in this study was qualitative methods. Then, data analysis techniques were carried out together with data collection during research with large and miniature tour questions, and domain analysis. This research was conducted in Bandung. To collect the data, observation, interviews and literature studies or review were conducted. As the result, this study found that the the Implementation of Spatial Planning Forces with Bandung City Spatial Planning from a conceptual, juridical and operational level is still not running. The information technology is to digitally document all activities carried out.